Biopolitics, life and body: some considerations from a Latin-American point of view - Alvarez, Luciana (2014)
We intend to get a close look at Foucault’s work on biopolitics with the aim of contrasting some of its aspects with the developments linked to the emancipatory and liberating potential of the notion of life (living corporeality) within the framework of Enrique Dussel’s Latin American Political Philosophy. We are interested in these theoretical approaches (Foucault’s biopolitics and Dussel’s Liberation Politics) given the political implications and prominence they grant to the notions of body and life in contemporary societies. The works we are interested in to contrast present different standpoints: In the first one, life is related to the exercise of political power, whereas in the second one its approach concentrates on political emancipation processes. We believe, however, that it is possible to find convergence points between them that allow us to explain, to a certain extent, the importance of the notion of life in contemporary societies. For this purpose, we will carry out an analysis of the notion of “counter behaviors,” a concept that Foucault briefly develops to explain how life has not been thoroughly integrated to technologies that dominate or run it but instead escape them ceaselessly.